2005
DOI: 10.1055/s-2005-837774
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Cyclic Nucleotide Phosphodiesterase Inhibition in the Vasorelaxant Activity of the Citrus-Fruits Flavonoid (±)-Naringenin

Abstract: The potential vasorelaxant, antioxidant and cyclic nucleotide phosphodiesterase (PDE) inhibitory effects of the citrus-fruit flavonoids naringin and (+/-)-naringenin were comparatively studied for the first time in this work. (+/-)-Naringenin (1 microM - 0.3 mM) did not affect the contractile response induced by okadaic acid (OA, 1 microM). However, (+/-)-naringenin relaxed, in a concentration-dependent manner, the contractions elicited by phenylephrine (PHE, 1 microM) or by a high extracellular KCl concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…5C). It is likely that the distinctly high dose required for the cardiac depressant effect of the essential oil, is due to by interference of PDE inhibitory constituents, which are known to be stimulants in the heart (Brain and Hoffman, 2001;Orallo et al, 2005), a pattern similar to that observed with papaverine. Thus, the co-existence of PDE inhibitory and CCB constituents in the essential oil is likely to offset the cardiac side-effects and offering added advantage when used for gut and airways hyperactivity disorders.…”
Section: Resultsmentioning
confidence: 78%
“…5C). It is likely that the distinctly high dose required for the cardiac depressant effect of the essential oil, is due to by interference of PDE inhibitory constituents, which are known to be stimulants in the heart (Brain and Hoffman, 2001;Orallo et al, 2005), a pattern similar to that observed with papaverine. Thus, the co-existence of PDE inhibitory and CCB constituents in the essential oil is likely to offset the cardiac side-effects and offering added advantage when used for gut and airways hyperactivity disorders.…”
Section: Resultsmentioning
confidence: 78%
“…The comparison of 1 with other flavonoids indicates that a 4Ј-hydroxy group in C-ring has a significant effect upon the inhibition of b-amylase. Most lavandulylated flavanones (1)(2)(3)(4)(5) showed much stronger inhibitory activities against both glycosidases in comparison to prenylated ones (6, 7). Moreover, lavandulylated chalcone, kuraridine (8), exhibited IC 50 value of 57 mM against a-glucosidase, which is the first report of a chalcone displaying glycosidase inhibition properties.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] In recent years, flavonoids have been the focus of target compounds for glycosidase inhibitor. For instance, genistein, 7) anthocyanins 8) and luteolin 9) showed potent inhibitory activities for glycosidases.…”
mentioning
confidence: 99%
“…It is known that AF contains several chemicals (Table 3), and of these components, naringin and hesperidin have been most widely recognized as having anti-ischemic effects that could potentially prevent Ca 2+ overload or intake by the cell (Calderone et al, 2004;Singh and Chopra, 2004). In more detail, it has been reported that hesperidin and hesperetin, a major metabolite of hesperidin in vivo significantly activated vasorelaxation through potassium channel activation (Calderone et al, 2004), and naringenin, a major metabolite of naringin in vivo significantly inhibited Ca 2+ uptake induced by phenylephrine in rat aorta (Orallo et al, 2005) and in voltage operated calcium channel in clonal rat pituitary GH C cells (Summanen et al, 2001). Reactive oxygen species and metabolites are known to play important roles in the pathogenesis of ischemia/perfusion and anoxia/reoxygenation injury.…”
Section: Discussionmentioning
confidence: 97%